The Stigma towards Seeking Help among Universities Students: A Cross-Sectional Study in Jordan - Ahmad Feras AlSamhori; Jehad Feras AlSamhori; Abdel Rahman Feras AlSamhori; Julia Abuaun; Nada AlAwamleh; Rnad Saleh (University Library System, University of Pittsburgh, 2023)
BACKGROUND: The study aims to assess university students' attitudes and stigmas regarding seeking mental health help, focusing on the barriers they face. Existing literature highlights the prevalence of social stigma, embarrassment, and fear among medical students, which hinder their willingness to seek psychiatric treatment despite the burden of mental illness. METHODS: The study is a cross-sectional examination of university students in Jordan. A self-administered English questionnaire with three domains and 31 questions was used. The first domain collected sociodemographic data. The second domain measured attitudes using the Attitudes Toward Seeking Professional Psychological Help Scale (ATSPPH), a higher score indicating a better help-seeking attitude. The third domain gauged stigma using the Stigma Scale for Receiving Psychological Help (SSRPH), a higher score indicating a higher degree of perceived stigma. A pilot test involving over 20 participants was conducted. Data analysis will be done via SPSS version 26. Normality was tested using the Shapiro-Wilk test. Chi-square, Mann-Whitney U and Kruskal-Wallis tests were used to assess associations between categorical and continuous variables. A significance level of p < 0.05 will be used. Finally, ethical considerations were obtained. RESULTS: In a study involving 1,151 participants. The average age of the participants was 22.35, with most identifying as female (70.7%) and single (95.1%). A majority had a monthly income exceeding 500 JDs, and around 60% lived in urban areas. Notably, 66.1% were medical students, and 88.3% were enrolled in public universities. Parental education was relatively high, with over 68% of mothers and 70% of fathers holding bachelor's degrees or higher. The study also delved into participants' mental health backgrounds, revealing that a significant portion had experienced the absence (27.6%) or death (22.7%) of first-degree relatives. A substantial number (71.5%) believed that mental illness carried a sense of embarrassment within their society, while 24.2% reported having family members who had experienced mental illness. The average score of ATSPPHS indicated that 84.7% had a negative attitude toward seeking professional help for emotional problems. Significant differences in attitudes were found across demographics, with females (p-value<0.001), urban residents (p-value=0.001), and those without first-degree relatives experiencing absence or death more likely to have a higher mean (p-value=0.001, 0.002, respectively). SSRPH also yielded important insights. The mean score was 11.39, with male participants, those with absent first-degree relatives, those who believed mental illness was embarrassing, and those with family members with mental illnesses tending to have higher scores, indicating higher stigma. Lastly, Spearman's correlation analysis revealed a weak negative association between ATSPPHS and SSRPH scales, suggesting that those with more positive attitudes toward seeking professional help tended to have lower stigma. CONCLUSION: In summary, the study shed light on the attitudes and stigma related to seeking professional psychological help among university students in Jordan. It found that negative attitudes were prevalent, particularly among certain demographic groups, and that attitudes were associated with the perception of stigma. These findings could inform interventions and educational programs to reduce stigma and promote a more positive attitude toward seeking mental health support.